Selective inhibition of autoimmune exacerbation while preserving the anti-tumor clinical benefit using IL-6 blockade in a patient with advanced melanoma and Crohn's disease: a case report. Issue 1 (December 2016) - Uemura, Marc; Trinh, Van; Haymaker, Cara; Jackson, Natalie; Kim, Dae; Allison, James; Sharma, Padmanee; Vence, Luis; Bernatchez, Chantale; Hwu, Patrick; Diab, Adi
Abstract Background Novel immunotherapies, or checkpoint inhibitors, targeting programmed cell death protein-1 (PD-1) and cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) have significantly improved outcomes for patients with numerous different cancer types. However, owing to their exclusion from clinical trials and risk for autoimmune exacerbation on these treatments, the impact on safety and degree of toxicity of these potentially life-prolonging therapies is not well characterized in patients with an underlying autoimmune disease or previous organ transplant. Case presentation We report a case of a patient with advanced melanoma and refractory Crohn's disease who was treated concurrently withpembrolizumab (anti-PD-1 antibody) andtocilizumab (anti-interluekin-6 receptor antibody). This novel treatment strategy was well tolerated and did not result in Crohn's disease exacerbation for at least 16 weeks. Importantly, this treatment resulted in marked, durable antitumor responses. Conclusions This outcome suggests that targeted immunosuppression combined with checkpoint inhibitors may hold promise as a treatment strategy for this unique patient population and may warrant additional study.